MODERN PROBLEMS, SOLUTIONS, AND PROSPECTS IN HYDRAULIC ENGINEERING (American Journal of Technology and Applied Sciences, 2025)
This article provides a comprehensive scientific analysis of the present state, urgent challenges, and future directions in the field of hydraulic engineering, focusing on the design, construction, operation, and sustainable management of hydraulic structures. It reviews the historical evolution and current typologies of major waterworks—dams, weirs, canals, barrages, reservoirs, and integrated irrigation and drainage systems—within the framework of their hydraulic, structural, ecological, and socio-economic functions. Emphasizing recent advances, it examines the integration of high-performance materials, computational fluid dynamics, digitalization, and ecological engineering in modern practice. The review highlights the complex interplay between anthropogenic activities, climate variability, and river basin processes, drawing on global case studies and the specific experience of Uzbekistan and Central Asia. Challenges such as sediment management, water scarcity, infrastructure aging, flood control, ecosystem fragmentation, and emerging climate extremes are critically assessed. The article discusses adaptation pathways including green infrastructure, risk-based design, remote sensing, real-time operation, and participatory governance. Based on the synthesis, recommendations are proposed to support resilient, sustainable, and efficient hydraulic engineering practice in the 21st century.